Analysis Factors Teachers Occupational Well-Being - Kholisna, Titin (Universitas Nusantara PGRI Kediri, 2024)
Teacher occupational well-being factors include various components that influence them both from a physical, social, economic, psychological and legal perspective. This research uses a quantitative development instrument which aims to develop an instrument in the form of items and factors/components so that adequate validity results are obtained. We have obtained the results of developing a total of 75 items on the teacher work welfare scale which have been tested on 23 teachers. By using exploratory analysis, valid item results with factor loading > 0.5 were obtained for 38 items with four factors formed from a rotated component matrix with item values ​​of 0.52 (lower) - 0.867 (higher). As a result of these factors, factors were named, namely factor 1 is recognition and satisfaction of professional work with a total of 13 items, factor 2 is self-development skills with a total of 9 items, factor 3 is administrative system support with a total of 9 items, factor 4 is balance of school culture with a total of 7 items. and this development instrument has obtained a reliability of 0.964.